If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X)(2) + 13 = 20 Reorder the terms for easier multiplication: 2X + 13 = 20 Reorder the terms: 13 + 2X = 20 Solving 13 + 2X = 20 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 2X = 20 + -13 Combine like terms: 13 + -13 = 0 0 + 2X = 20 + -13 2X = 20 + -13 Combine like terms: 20 + -13 = 7 2X = 7 Divide each side by '2'. X = 3.5 Simplifying X = 3.5
| 8a+3=-19 | | 9x-2x=52 | | 6x-2=-28 | | 5x+19y=-7 | | 5x-100=x-20 | | x-3-8=-1 | | (X)(3)-5=-1 | | 2x+7-(5-4x)=3 | | -9(16-f)=(1-3f) | | 2a-2b-3c=1.5 | | -x-7=-8+x | | z-8=0 | | x-20=3y | | 2x(2x-1)=5 | | f(x)=10x^2-20x+16 | | k-3=8 | | x+4/x+7 | | 7n+10=78 | | 4(2x-3)=8+(2x-4) | | 1/4-5=27 | | X^6-2x^4-x^2+2=0 | | (n-5)*7=70 | | 4x^2-23x+72=0 | | 3+2i/6+5i | | 6x/38=48 | | 0=x^2+4x-32 | | x^2-19x+25=0 | | 0=x^2+10x+24 | | 1.24=x2-x1/3 | | 0=(x-4)(x+2) | | 3x=999 | | 2x=7.81 |